2006
DOI: 10.1177/0885328206055316
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin Immobilization using Water-soluble Carbodiimide on Poly-L-lactic Acid for Enhancing Initial Fibroblast Attachment

Abstract: The aim of this study is to evaluate the influence of fibronectin immobilization on poly-L-lactic acid (PLA) films on the initial attachment of human gingival fibroblasts. Carboxylic acid groups are chemically introduced on the PLA films' surface by surface hydrolysis with 0.5 M NaOH. The contact angle of PLA surface with respect to double-distilled water decreases significantly after NaOH hydrolysis. X-ray photoelectron spectroscopy (XPS) also reveals significantly higher intensities of C C¼O /C C-O after NaO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…NaOH treatment is a simple technique for modifying degradable polymeric materials such as PLA and PLGA. Nagai et al 21) evaluated the hydrolysis time of PLA for surface hydrolysis. They reported that 3 hours of NaOH treatment produces the lowest contact angle with respect to double-distilled water.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NaOH treatment is a simple technique for modifying degradable polymeric materials such as PLA and PLGA. Nagai et al 21) evaluated the hydrolysis time of PLA for surface hydrolysis. They reported that 3 hours of NaOH treatment produces the lowest contact angle with respect to double-distilled water.…”
Section: Discussionmentioning
confidence: 99%
“…Fuse et al 25) and Nagai et al 21) reported an improvement in the biological activity of P LA, such as cell attachment, biocompatibility, immobilized fibronectin, and cell-adhesive protein, on the surface of a PLA film following NaOH surface hydrolysis and condensation reactions using water-soluble carbodiimide. The result demonstrated that fibronectin immobilization enhanced cell attachment and proliferation on the surface of the PLA film.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present results were consistent with our previous study. Fibronectin immobilization on PLA surface significantly enhanced the number of initially (90 min cell culture) attached human gingival fibroblast 18) . Other studies reported the efficacy of collagen or fibronectin immobilization for cell attachment and proliferation.…”
Section: Discussionmentioning
confidence: 98%
“…Contact angles were significantly decreased by NaOH treatment for 3 hr. Our previous study reported the introduction of carboxylic acid groups onto a PLA film surface by NaOH hydrolysis method 18) . PLA film was treated by NaOH for 3 hr.…”
Section: Discussionmentioning
confidence: 99%